An Analysis of Students' Saturation and Learning Interest when Studying Offline in Biology Subject at Darus Sholah High School in Jember - Hidayati, Kamilia Liyana; Annisa, Maulida Dwi; Agustin, Alina Dini; Vebrian, Mohammad Aldi (META: Journal of Science and Technological Education, 2023)
This study's objective was to investigate the causes of student boredom and interest in offline learning in biology classes at Darus Sholah High School in Jember. The research method employed is descriptive qualitative. The participants in this research were 21 XB class. Observational data was collected through direct interviews with students. As there were both full day and full time pupils at Darus Sholah High School, the Google form and questionnaire sheets were used to collect data via an open questionnaire distributed to XB class students. The interactive analysis technique developed by Miles and Huberman was used to analyze the data. The results indicated that the saturation factor for student learning was poor. The results of research on the factors that influence students' interest in learning indicate that students have a strong interest in learning biology. This demonstrates that the level of learning saturation felt by students is poor and does not diminish their interest in offline biology courses.